Kesulitan Belajar Mata Kuliah Kemuhammadiyahan I Bagi Mahasiswa Non Muslim di Program Studi PGSD Universitas Muhammadiyah Palangka Raya - Fella Yati (LP2M IAIN Palangka Raya, 2015)
The problems of the study in this research were 1) the students’ difficulty in learning about the course of Kemuhammadiyahan I and 2) the internal and external factors that caused the students’ difficulty in learning for non-Muslim students for Therefore, the purpose of this study was 1) to describe the difficulty in learning that was faced by non-Muslim students in attending Kemuhammadiyahan I at PGSD Study Program, UMP, and 2) to describe the internal and external factors that caused the non-Muslim students’ difficulty in attending Kemuhammadiyahan I at PGSD Study Program, UMP. The result of the study showed that (a) there was no difficulty in learning found from non-Muslim students in Kemuhammadiyahan I, this result was based on the score of Kemuhammadiyahan I from the total of 5 students who became the subject of the study. (b) Having reviewed from the internal and external factors, from 16 non-Muslim students who took Kemuhammadiyahan I, there were 5 students who were chosen as the subjects. Concerning the internal factor, it was due to the students’ lack of motivation, interest, and also attention to the course. The results showed it does not occur non-Muslim students' learning difficulties in the course Kemuhammadiyahan I